An Immunocompetent HIV-Negative Elderly Patient with Low-Grade Fever, Generalized Lymphadenopathy, Splenomegaly, and Acute Phase Response: Do Not Forget Castleman Disease - Kalliopi Azariadis; Maria Ioannou; Kalliopi Zachou; George N. Dalekos (Case Reports in Infectious Diseases)
Multicentric Castleman disease (MCD) is a rare lymphoproliferative disorder that mainly affects middle-aged patients with human immunodeficiency virus (HIV) infection. However, HIV-negative patients can also be affected representing a small proportion of the total MCD cases. Of note, recent studies from China in HIV-negative patients with MCD have suggested that the onset of the disease can be observed in younger age than previously thought. If undiagnosed and untreated, the MCD has a poor prognosis and may progress to lymphoma. We present an 82-year-old immunocompetent male patient who was admitted to our department because of low-grade fever, cachexia, anasarca, hepatosplenomegaly, and generalized lymphadenopathy. Laboratory findings showed anemia and increased markers of inflammation including hyperferritinemia and polyclonal hyperglobulinemia. Infectious causes including HIV were ruled out. Histological examination of a cervical lymph-node revealed lesions supportive of MCD diagnosis. Of note, the outer-zone plasmablasts’ nuclei stained positive for human herpesvirus-8 (HHV8). The patient received 4 cycles of cyclophosphamide, vincristine, and dexamethasone with regression of all symptoms. This case underlines that HHV8-associated MCD should be considered as a rare cause of generalized lymphadenopathy even in HIV-negative immunocompetent patients when other causes have been appropriately excluded because a timely diagnosis can be life-saving.